Instream wood loads in old-growth and non-old-growth montane forests - Jackson, Karen, author; Wohl, Ellen, advisor; Rathburn, Sara, committee member; Bledsoe, Brian, committee member (Colorado State University. Libraries, 2014)
Although several studies document instream wood loads and geomorphic effects in subalpine forests of the southern Rocky Mountain region, little is known of instream wood loads in lower elevation, montane forests of the region. This study focuses on comparing instream wood loads and associated stream geomorphological responses between montane forest stands in the Arapahoe-Roosevelt National Forest of differing age and disturbance history: (i) old-growth forests versus younger, minimally impacted forests, and (ii) healthy forest stands versus stands with greater than 25% of trees infested by mountain pine beetles. Wood loads of 33 study sites were measured in pool-riffle reaches, along with cross section surveys, pool volume, and sediment volume. Wood loads were standardized to reach length, slope, bankfull width, drainage area, and floodplain area. The significance level was ultimately increased from of α = 0.05 to 0.10 and used for all statistical analyses. Using a pairwise t-test, the standardized wood loads were tested based on stand age. There were significantly larger instream wood volumes and jam volumes in old-growth montane forests. Jam frequencies in old-growth forests were significantly higher (Kruskal-Wallis test). Residual pool volume and sediment storage (standardized to slope) were significantly greater in old-growth stands. There was no significant difference between wood loads in mountain pine beetle infested and healthy forest stands. Using the best subset regression method, log10 (elevation), stand age, and mountain pine beetle infestation were the best predictors of all measures of wood volume - total, instream, and floodplain. Even though infested stand wood loads means were not significantly different than healthy wood load means, multivariate analysis found stand health to be an important predictor of wood loads. Instream wood loads were comparable to previous Colorado Front Range subalpine values. Jam frequencies were lower in montane streams than Front Range subalpine streams and Pacific Northwest streams. Forest managers should take stand age into consideration when understanding montane streams, whereas recent mountain pine beetle infestation may be less of an issue. Over the next century, beetle infestation may become more relevant, but as of now there is no significant addition of wood to streams.
Keywords: instream wood; mountain pine beetle; large woody debris